2019
DOI: 10.28982/josam.605123
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of skin to epiglottis length for difficult airway prediction by ultrasonography in obese pregnant women: Prospective cohort study

Abstract: How to cite / Atıf için: Kantekin ÇÜ, Erkoç MF, Talih G. The measurement of skin to epiglottis length for difficult airway prediction by ultrasonography on obese pregnant women: Prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, in their study conducted with 120 obese patients in 2018, Özdilek et al [21] reported that neck circumference was not a risk factor for difficult mask ventilation or for difficult laryngoscopy. In line with studies using ultrasound measurement, which reported that large neck circumference contributes to difficult intubation due to fat deposition in the anterior soft tissue of the neck, Raju Vegesna et al [27] showed that neck circumference has the highest significance as a parameter in terms of difficult intubation [28]. In their study that compared 123 obese and 125 non-obese patients, Kim et al [26] found that neck circumference/thyromental distance ratio is a better predictor of difficult intubation than the Mallampati classification or neck circumference measurement alone.…”
Section: Discussionmentioning
confidence: 67%
“…However, in their study conducted with 120 obese patients in 2018, Özdilek et al [21] reported that neck circumference was not a risk factor for difficult mask ventilation or for difficult laryngoscopy. In line with studies using ultrasound measurement, which reported that large neck circumference contributes to difficult intubation due to fat deposition in the anterior soft tissue of the neck, Raju Vegesna et al [27] showed that neck circumference has the highest significance as a parameter in terms of difficult intubation [28]. In their study that compared 123 obese and 125 non-obese patients, Kim et al [26] found that neck circumference/thyromental distance ratio is a better predictor of difficult intubation than the Mallampati classification or neck circumference measurement alone.…”
Section: Discussionmentioning
confidence: 67%